Os efeitos da desjudicialização da usucapião diante dos aspectos notariais e registrais - Pires, Dara dos Santos (My University, 2025)
This monograph sought to analyze how extrajudicial adverse possession, an innovation that was introduced into the Legal System by the Code of Civil Procedure (Law No. 13,105/2015), with the inclusion of art. 216-A in Law no. 6,015/1973 (Public Records Law) and concomitantly with this, the regulation of the guidelines through Provision 65/2017 of the National Council of Justice, which facilitated the obtaining of property rights and established the importance and speed of the dejudicialization of adverse possession, as well as the efficiency in the procedures for analyzing the entry of the title and carrying out the registration, before the Property Registry Office,thus preventing the notary system from being overloaded. To this end, the research was divided into four moments. Initially, there was the introduction of Real Rights, on property, possession and their effects on adverse possession. Next, the analysis of adverse possession of properties, its preliminary notions and its concept was carried out, as well as the social function of the property and the types of adverse possession were conceptualized. Afterwards, it was discussed about extrajudicial usucapion, its requirements, characteristics and procedures, in addition to being discussed about the documents necessary for the entry of the usucapion request. Finally, the notarial and registration aspects of extrajudicial adverse possession were demonstrated, within the scope of the Notary's Office and the Property Registry, so that the central theme of this work was subsequently introduced, which was the analysis of the effects of the dejudicialization of adverse possession. To develop this article, the hypothetical deductive approach method was used, which aimed to creat hypotheses so that it was possible to respond to the proposed problem. It was concluded that, through the effective distribution of procedures, compliance with deadlines, assertive communication between employees and the applicant, in addition to due training of the team so that the client would not suffer the consequences of overloading the Notary's system, given the new possibility extrajudicial. Therefore, it became clear that extrajudicial adverse possession is the fastest and most effective method for regularizing property. [resumo fornecido pelo autor]
A presente monografia buscou analisar como a usucapião extrajudicial, inovação que foi introduzida no Ordenamento Jurídico pelo Código de Processo Civil (Lei n°. 13.105/2015), com a inclusão do art. 216-A na Lei n°. 6.015/1973 (Lei de Registros Públicos) e concomitantemente a isso, a regulamentação das diretrizes através do Provimento 65/2017 do Conselho Nacional de Justiça, que facilitou a obtenção do direito de propriedade e firmou a importância e a celeridade da desjudicialização da usucapião, bem como a eficácia nos procedimentos da análise da entrada do título e a efetivação do registro, perante o Cartório de Registro de Imóveis, assim, evitando que o sistema cartorário ficasse sobrecarregado. Para tanto, dividiu-se a pesquisa em quatro momentos. Inicialmente, houve a introdução sobre os Direitos Reais, sobre a propriedade, a posse e os seus efeitos para usucapião. Em seguida, foi realizada a análise da usucapião de imóveis, suas noções preliminares e o seu conceito, assim como foi conceituada a função social doimóvel e as espécies da usucapião. Após, foi abordado sobre a usucapião extrajudicial, seus requisitos, características e procedimentos, além de ter sido abordado sobre os documentos necessários para o ingresso do pedido da usucapião. Por fim, foi demonstrado os aspectos notariais e registrais da usucapião extrajudicial, no âmbito do Tabelionato de Notas e do Registro de Imóveis, para que na sequência, fosse introduzido o tema central deste trabalho, que foi a análise dos efeitos da desjudicialização da usucapião. Para que fosse desenvolvido o presente artigo foi utilizado o método de abordagem hipotético dedutivo, que objetivou a criação das hipóteses para que fosse possível responder ao problema proposto. Foi concluído que, mediante a distribuição efetiva dos procedimentos, com o cumprimento dos prazos, comunicação assertiva dos colaboradores com o requerente, além do devido treinamento da equipe para que o cliente não sofresse as consequências da sobrecarga do sistema do Cartório, diante da nova possibilidade do extrajudicial. Sendo assim, ficou evidenciado que a usucapião extrajudicial é o método mais célere e eficaz para a regularização da propriedade. [resumo fornecido pelo autor]
Keywords: Usucapião; Direitos reais; Registro de imóveis; Direito notarial e registral; Registro de imóveis